2010
DOI: 10.3847/aer0009068
|View full text |Cite
|
Sign up to set email alerts
|

A National Study Assessing the Teaching and Learning of Introductory Astronomy Part II: The Connection between Student Demographics and Learning

Abstract: This is the second in a series of reports on a national study of the teaching and learning of astronomy in general education, nonscience major, introductory college astronomy courses ͑hereafter referred to as Astro 101͒. The analysis reported here was conducted using data from nearly 2000 students enrolled in 69 Astro 101 classes taught across the country. These students completed a 15-question demographic survey, in addition to completing the 26-question Light and Spectroscopy Concept Inventory ͑LSCI͒ pre-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 14 publications
3
24
0
Order By: Relevance
“…The first is that all of the data were collected at a single institution. While there is no reason to believe that the students at this institution are dramatically different from students across the USA in terms of their demographics, motivation toward general education coursework, or astronomy knowledge (Rudolph et al, 2010;Slater et al, 2001), testing this claim was beyond the scope of this study. A validation study that includes ASTRO 101 courses from multiple institutions is currently in progress.…”
Section: Limitations Of the Research Designmentioning
confidence: 95%
See 1 more Smart Citation
“…The first is that all of the data were collected at a single institution. While there is no reason to believe that the students at this institution are dramatically different from students across the USA in terms of their demographics, motivation toward general education coursework, or astronomy knowledge (Rudolph et al, 2010;Slater et al, 2001), testing this claim was beyond the scope of this study. A validation study that includes ASTRO 101 courses from multiple institutions is currently in progress.…”
Section: Limitations Of the Research Designmentioning
confidence: 95%
“…2257-2286 of such studies are only recently impacting the introductory astronomy course for non-science majors in meaningful ways. Hereafter, we refer to this introductory course, a popular one within USA's tertiary institutions (Fraknoi, 2001;Partridge & Greenstein, 2003;Rudolph, Prather, Brissenden, Consiglio, & Gonzaga, 2010), as 'ASTRO 101'. Both traditional and action research studies in ASTRO 101, as well as their brethren in other science disciplines, are affecting how instructors design their courses to better facilitate meaningful learning.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work has shown that there has been little change in students' science knowledge responses over time and that students' demographic information explains a minimal amount of the variance in their knowledge scores [40,42]. However, other work has also shown that (a) introductory astronomy courses are popular among a broad range of students [1,2,21], (b) the number of college science courses has been shown to be a strong predictor of civic scientific literacy, defined as having "(1) a basic vocabulary of scientific terms and constructs; and (2) a general understanding of the nature of scientific inquiry" (p. 273) in U.S. adults [14], and (c) a positive relationship exists between interest and attitudes and individuals' understanding in science [26][27][28]. In addition, there is ongoing interest in building students' scientific literacy comprised of multiple facets, including scientific knowledge and students' ability to locate and use information (information literacy) [9,16,17].…”
Section: B Research Questionsmentioning
confidence: 99%
“…Astronomy 101 courses are popular elective courses that attract a wide range of students and thus provide a unique opportunity to affect students from a variety of nonscience disciplines who take these courses. The students who take introductory astronomy courses as nonmajors represent a wide range of society who are well educated but may not enter a science or technical careers [21]. These courses often recruit students who are averse to math and looking to fulfill their general education science requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to an introductory astronomy course, students' exposure to astronomy is typically limited to middle school science curricula and, according to the National Science Board's Science and Engineering Indicators [35], information from various media outlets such as television documentaries and movies. Additionally, most of these students will not take any further astronomy classes following the introductory astronomy course [36], and the understanding these students gain from an introductory astronomy course will serve as the foundation of their astronomy knowledge. Therefore, providing introductory astronomy courses that are based on a modern view of the Universe and a modern treatment of science, which address and build on the ideas students bring to the classroom, can contribute to the development of a more scientifically literate society.…”
Section: Introduction a Background And Motivationmentioning
confidence: 99%